Female Self-affirmation and Self-fulfilment in Nwapa’s One is Enough (1981) (International Journal of Scientific Research and Management (IJSRM), 2022)
The portrayal of women in most African male-authored novels which appeared before and after the independences, frustrated many African female intellectuals. The latter considered that some African men writers have not presented a fair image of women in their writings. For them, they have marginalised and relegated women to second-class citizens. Thus, these female intellectuals set out in their turn to write literary texts in which they correct what they considered to be shortcomings in African male writings. Among these women writers stands out Flora Nwapa who deals in One is Enough (1981) with issues such as gender, sexuality, tradition, postcolonialism, modernity, culture, sociology, psychology and materialism in Nigerian society in particular and African societies in general. Leaning on African feminism, postcolonialism, sociology and psychology as theories, this article analyses female self-fulfilment and self-affirmation in One is Enough. In this perspective, the paper zeroes in on the awareness-raising about women’s right to defend their opinion and physical integrity. It also sheds light on the possibility for women to find fulfilment outside marriage.